(untitled) (EDUCATION IN THE 21ST CENTURY, 2024)
The methodological validity of the article is to introduce students to reading not only by viewing a filmed literary work, but also by actually familiarizing themselves with the work itself. Film adaptations of works by contemporary authors expand the possibilities of getting to know them, as well as communicating through television and radio programs, attending author evenings, presentations of new works, and participating in interactive discussions. By drawing students’ attention to film adaptations of new literary works, we seem to involuntarily stimulate their interest in reading. The article reveals the features of the new female image in literature, the author’s ability to briefly, but at the same time meaningfully present an entire historical era, to expressively present to the reader the ethnoculture of the Tatar people. The work notes the need to familiarize students with modern authors and attract students’ attention to reading through the analysis of filmed works, which makes it possible to awaken interest in literary creativity itself and the creation of new images in Armenian literature.